Perbedaan Kinerja Bank Perekonomian Rakyat (BPR) Berdasar Kondisi Sebelum, Saat Pandemi dan Awal Transisi Pandemi - Rizki, Otot Bayu; Putra, I Nyoman Nugraha Ardana (Universitas Mataram, 2024)
During the Covid-19 pandemic, many economic sectors experienced significant disruption. This also has an impact on the banking sector, including BPR which are financial institutions that play a key role in supporting economic growth at the local level by providing banking services to the MSME sector. This research aims to examine whether Covid-19 has an impact on the banking financial performance of the People's Economic Bank by comparing the performance of BPRs before, during and after the pandemic. The data used is secondary originating from 2018-2021 publications. There are several financial performance ratios used, including Liquidity (Loan Deposit Ratio), Non-Performing Loans, Profitability (Return On Assets), Capital (Capital Adequency Ratio) and operations (Operating Costs and Operating Income). The data was processed using a Mann-Whitney U test using the SPSS 23 application. This research indicate that the performance of BPR banks in the NTB region is able to maintain stability and consistent financial performance in several indicators, such as NPL, ROA, LDR, BOPO and CAR before, during and early in the transition to the Covid-19 pandemic.